Evaluation of mechanical properties and determination of the optimal concentration of a new carbonyl-rich graphene oxide in cementitious composites - Aldo Ribeiro de Carvalho; Marcela Martins Carrara; Gabriela dos Santos Pacífico; Natany Pinho Rosa; Letícia Lopardi Leal; Marina Costa Totti; Nayton Claudinei Vicentini; Alessandro Henrique de Lima; Welber Gianini Quirino; Thaís Mayra de Oliveira (Case Studies in Construction Materials)
Nanomaterials represent one of the many alternatives currently under study that have the potential to store carbon in cementitious composites, thereby preventing their release into the atmosphere. When graphite is properly manipulated, graphene oxide is produced, a nanomaterial with various functional groups. By adapting the Hummers’ method, it is possible to create graphene oxide rich in carbonyl (CGO), which becomes the predominant functional group of the nanomaterial. Studies assessing the impact of adding CGO to Portland cement concretes have not been found in the literature. Hence, this study presents significant novelty by examining the physical, mechanical, and microstructural properties of concretes with CGO additions at concentrations of 0.02 %, 0.03 %, and 0.05 % by mass of cement. To achieve this, tests were conducted for specific gravity, void index, water absorption, ultrasonic pulse velocity, tensile and compressive strength at 28 and 365 days, as well as static and dynamic modulus of elasticity. Subsequently, microstructural properties were evaluated using scanning electron microscopy, X-ray diffraction, and thermal conductivity analysis. After 365 days, the durability of carbonation was also assessed using a computational model developed in MATLAB to more accurately calculate the carbonated area. It was noted that incorporating CGO improves the mechanical properties of concrete, diminishes carbonation over time, and boosts the thermal conductivity of the composite. The optimal CGO composition is 0.02 %, resulting in a 33.22 % surge in compressive strength and a 17.94 % increase in tensile strength. While other CGO concentrations also enhanced the composite, they displayed CGO agglomeration, diminishing efficiency compared to the control concrete.